DDT water contamination and the impact on water quality access in Africa in relation to human health risks - Makgoba, Lethabo (Department of Public Health and Family Medicine, 2026)
DDT usage is prohibited in developed nations but exempted for use in indoor residual spraying (IRS) in developing countries, including African countries. No previous review of DDT residues in water resources has been conducted before in Africa. The study aimed to provide a review of available research investigating the levels of DDT residues in water sources in Africa and to assess the consequent human health risks. A scoping review of published studies conducted in Africa was facilitated through an extensive electronic search using PubMed, Web of Science, EBSCO HOST, and Scopus. A total of 20 articles were reviewed. The DDT concentrations varied between no detection to 81. 2 µg/l, with 35% of the studies having found DDT concentrations that exceeded the WHO drinking water guideline of 1 µg/l, in the sampled water sources. South Africa (81. 2 µg/l) and Egypt (5.62 µg/l) had the highest DDT concentrations in the sampled water sources. DDT levels were found to be higher during the wet season. Moreover, water from taps, rivers, reservoirs, estuaries, wells, and boreholes containing DDT residues was used to provide drinking water. Five studies conducted health risk assessments, and two studies found cancer risk values that exceeded the permissible limits in water sampled from sources that were used as a source of drinking water. Contrastingly, the non-carcinogenic risk values in the studies were below a hazard quotient of 1. DDT residues were detected throughout the year in African water systems. In conclusion, evidence of risks to human health was found as the concentration of DDT residues exceeded the WHO drinking water guidelines and/or cancer risk permissible limits in sampled drinking sources in African water systems. Alternative methods for malaria vector control should be investigated. Larger studies that include risk assessments and seasonal monitoring of DDT residues in multiple water sources are recommended.